2008
DOI: 10.1258/jms.2008.007086
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term storage of filter paper blood samples on neonatal thyroid stimulating hormone, thyroxin and 17-alpha-hydroxyprogesterone measurements

Abstract: Objectives Clinical laboratories store filter paper samples used in neonatal screening for various periods of time after performing hormonal measurements. However, due to lack of data concerning specimen stability, it is unclear for how long these samples should be stored. The objective of this study is to determine the stability and reproducibility of thyroid-stimulating hormone (TSH), thyroxine (T 4 ) and 17-hydroxyprogesterone (17-OHP) measurements in filter paper blood samples stored for up to 60 months. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 10 publications
2
20
0
Order By: Relevance
“…The stability of TSH in this study (30 days at RT and up to 60 days in the refrigerator or freezer) was shorter than the 36 months reported by Lando and cols. (6) for samples collected from newborns on filter paper and stored in a refrigerator (2-8 o C), and also shorter than the 2.7, 4.1 and 6.5 years for samples stored at RT, 4 o C and -20 o C, respectively, reported by El Ezzi and cols. (7).…”
Section: Stability Of Tsh In Blood Spotsmentioning
confidence: 60%
See 3 more Smart Citations
“…The stability of TSH in this study (30 days at RT and up to 60 days in the refrigerator or freezer) was shorter than the 36 months reported by Lando and cols. (6) for samples collected from newborns on filter paper and stored in a refrigerator (2-8 o C), and also shorter than the 2.7, 4.1 and 6.5 years for samples stored at RT, 4 o C and -20 o C, respectively, reported by El Ezzi and cols. (7).…”
Section: Stability Of Tsh In Blood Spotsmentioning
confidence: 60%
“…Although the pertinent literature is quite limited (2)(3)(4)(5)(6)(7)(8), it is undeniably important to establish the best drying and storage conditions of blood samples collected on filter paper for newborn screening. The samples are frequently exposed to different climate conditions during drying and transport to the laboratories, a fact that may influence the test results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was later confirmed by Elvers et al 7 . A recent report 8 showed that screening of filter papers is reliable for TSH and TT4 after storage of specimens for three years. However, this study tested the stability of filter spots only at 4°C–8°C.…”
mentioning
confidence: 71%